Productivity Spillovers from Foreign Direct Investment: What If Productivity is No Longer a Black Box? - Thang, Tran Toan (UI Scholars Hub, 2011)
While the positive productivity spillover from Foreign Direct Investment (FDI) to domestic owned firms in host countries is unequivocally emphasized in theory, the empirical evidence is contradictory. This paper, based on firm level data in Vietnam (enterprise census, 2000-2005), provides more inside on that. Using time-varying stochastic frontier approach, the study decomposed the change of productivity into technical change, technical efficiency change and scale efficiency change. The evidence from estimating the spillovers in each corresponding components suggest that horizontal FDI bring negative spillovers, mainly to technical change but positive spillovers to technical efficiency. Vertical FDI also have mixed impacts to domestic owned firm’s productivity.